Tuberculosis - Landau, Elaine (New York : F. Watts, 1995)
Discusses the history of tuberculosis, how attitudes towards it have changed, how it is transmitted, its most common symptoms, and what can be done to prevent the spread of this disease.
Includes bibliographical references and index.
Booklist.
School Library Journal.
Wilson's Junior High School.
Young Adult
Keywords: Tuberculosis; Diseases; Tuberculosis; Diseases; Tuberculosis